On Messages - Scott, Bernard CE (Journal of Sociocybernetics, 2018)
In this paper, I discuss the concept of a ‘message’ as applied to the different forms of communication: between man and machine, between machine and machine and between man and man. The term ‘message’ can refer to a relatively simple cause and effect interaction. An example is the transmission of a mechanical signal that, when decoded by a receiving system, triggers a standard response. It can also refer to the much more subtle and complex case where recipients construct meanings on the basis of the messages they receive. I contend that it is only in this latter case that we can properly refer to the interaction as a ‘conversation’. In the paper I present cybernetic models of these two usages. I relate the abstract discussion to current developments concerned with man-machine interaction and the development of a ‘global brain’.